Gut Microbiota of Drosophila subobscura Contributes to Its Heat Tolerance and Is Sensitive to Transient Thermal Stress - Jaramillo, Angélica; Castañeda, Luis E. (Frontiers in Microbiology, 2021)
Global warming impacts the fitness of animals, leading to increased extinction risk in ectotherm species. Gut microbiota can contribute to host physiology leading to an increase of resistance to abiotic stress conditions. For instance, temperature has profound effects on ectotherms, and the role of the gut microbiota on thermal tolerance of ectotherms is a matter of recent research. However, most of these studies have been focused on single static temperatures instead to evaluate the thermal tolerance in a wide range of stressful temperatures. Additionally, there is evidence supporting that the gut microbiota is sensitive to environmental temperature, which induces changes in its composition and diversity. These studies have been evaluated the effects of thermal acclimation (> weeks) on the gut microbiota, but we know little about the impact on transient thermal stress on the composition and diversity of the gut microbiota. Thus, we investigated the role of the gut microbiota on heat tolerance of Drosophila subobscura by measuring the heat tolerance of conventional and axenic flies exposed to different heat stressful temperatures (35, 36, 37, and 38ºC), and estimating the heat tolerance landscape for both microbiota treatments. Conventional flies exposed to mild heat conditions exhibited higher thermal tolerance than axenic flies, whereas at higher stressful temperatures there are no differences between axenic and conventional flies. We also assessed the impact of transient heat stress on the taxonomical abundance, diversity, and community structure of the gut microbiota, comparing non-stressed flies (exposed at 21ºC) and heat-stressed flies (exposed at 34ºC) from both sexes. Bacterial diversity indexes, bacterial abundances, and community structure changed between non-stressed and heat-stressed flies and this response was sex-dependent. In general, our findings provide evidence that gut microbiota influences heat tolerance, and that heat stress modifies the gut microbiota at taxonomical and structural levels. These results demonstrate that gut microbiota contributes to heat tolerance and is also highly sensitive to transient heat stress, which could have important consequences on host fitness, population risk extinction, and vulnerability of ectotherms to current and future climatic conditions.